How fishing pressures and environmental changes can impact the mean size of fish resources: a case study of small pelagics in the Adriatic Sea - Roberto Cacciamani; Valentina Caserta; Stefano Guizzardi o Guicciardi; Alberto Santojanni; Sabrina Colella; Filippo Domenichetti; Fortunata Donato; Silvia Angelini (Frontiers in Marine Science, 2025)
Small pelagic fish, such as European anchovy ( Engraulis encrasicolus ) and sardine ( Sardina pilchardus ), play a key ecological and economic role in the Adriatic Sea. In recent decades, both species have shown a marked decline in mean body size, raising concerns about the combined impacts of fishing and environmental change. To investigate the main drivers behind this trend, we analyzed 20 years (2000–2021) of fishery-dependent data on weighted mean length ( wML ) derived from Length Frequency Distributions (LFDs) of catches landed in two major Adriatic fishing harbors, Chioggia and Ancona. Generalized Additive Models (GAMs) were applied to explore the relationships between wML , fishing effort and key environmental variables (chlorophyll-a, sea surface temperature, salinity, sea surface height and Po River discharge), incorporating both spatial ( Harbor ) and temporal dimensions ( Time and Season ). Our results indicated that anthropogenic pressures, particularly the interaction between fishing activity ( Fleet ) and long-term temporal dynamics ( Time ), were the dominant contributors to size reduction. This interaction reflects how long-term exploitation patterns have intensified over time despite nominal reductions in fleet size, suggesting cumulative fishing impacts and limited recovery capacity. Environmental variables contributed to explaining the observed patterns but to a lesser extent, suggesting species-specific and spatially structured responses. Overall, this study highlights that historical overexploitation remains the primary driver of body-size decline in the Adriatic small pelagic species. However, the possibly influence of the environmental variables in the dynamics of these species suggest the development of adaptive, ecosystem-based management strategies that integrate historical fishing pressure, current effort distribution and environmental variability to promote the recovery and resilience of these key fishery resources.

“New records of rare species in the Mediterranean Sea” (October 2021) - KONSTANTINOS TSAGARAKIS; SANDRA AGIUS DARMANIN; SARA A.A. AL MABRUK; ROCCO AURIEMMA; ERNESTO AZZURRO; NICHOLAS BADOUVAS; RIGERS BAKIU; MICHEL BARICHE; PIETRO BATTAGLIA; FEDERICO BETTI; DIEGO BORME; ROBERTO CACCIAMANI; et al. (Mediterranean Marine Science, 2021)
“New records of rare species in the Mediterranean Sea” (October 2021)

High resolution climate precipitation analysis for north-central Italy, 1961–2015 - Valentina Pavan; Gabriele Antolini; Roberto Barbiero; Nicola Berni; Fabio Brunier; Carlo Cacciamani; Anselmo Cagnati; Orietta Cazzuli; Andrea Cicogna; Chiara De Luigi; Enzo Di Carlo; Marco Francioni; et al. (Climate Dynamics, 2019)